Changes in household use of disinfectant and cleaning products during the first lockdown period in France - Emilie Pacheco Da Silva; Raphaëlle Varraso; Laurent Orsi; Emmanuel Wiernik; Marcel Goldberg; Christophe Paris; Léopold K. Fezeu; Céline Ribet; Rachel Nadif; Fabrice Carrat; SAPRIS study group; Mathilde Touvier; et al. (BMC, 2024)
Abstract Background Few studies evaluated the use of Household Disinfectant and Cleaning Products (HDCPs) during the COVID-19 pandemic, but no population-based cohorts used longitudinal data. We studied changes in HDCPs during the first lockdown, based on longitudinal data from the French population-based NutriNet-Santé and CONSTANCES cohorts. Methods Based on standardized questionnaires on household cleaning tasks in 2018-2019 and around the first lockdown in France (March17-May3 2020), we compared the duration of weekly use of HDCPs (< 1 day/week, < 10 min/week; 10-30 min/week; > 30 min/week) and the household cleaning help (yes/no) before and during the lockdown period by Bhapkar and McNemar's tests. Moreover, we assessed self-reported changes in the frequency of HDCPs during the lockdown from before (unchanged/increased). Results Analyses were carried on 31,105 participants of NutriNet-Santé (48 years, 75% women, 81% ≥ high school diploma) and 49,491 of CONSTANCES (47 years, 51% women, 87% ≥ high school diploma). During the lockdown, compared with 2018-2019, duration of HDCPs use increased (> 30 min; NutriNet-Santé: 44% versus 18%; CONSTANCES: 63% versus 16%) and household help decreased (NutriNet-Santé: 5% versus 40%; CONSTANCES: 3% versus 56%). Regarding the frequency of HDCPs use, 55% of participants of NutriNet-Santé (57% women/49% men) and 83% of CONSTANCES (86% women/81% men) reported an increased use since the beginning of the lockdown, significantly higher among women (p < 0.0001). Conclusions The frequency and duration of weekly use of HDCPs has significantly increased since the pandemic. As the use of HDCPs is associated with health issues, further studies are now needed to evaluate the potential health impacts of these changes.